The Role of Pancasila Perspective Accounting in Overcoming The Trap of Online-Based Loans: A Phenomenological Study of Accountants - Bornok Situmorang; Heru Tjaraka; Santi Novita (Universitas Swadaya Gunung Jati, 2025)
Accountants are a group of people who have a good level of financial literacy. However, the trap of online-based loans has penetrated all levels of society, even accountants. Pancasila perspective accounting offers principles and values that can unravel financial problems such as the trap of online-based loans. Therefore, this study is essential. This study aims to explore and interpret the experience of accountants as online-based loan debtors. This study uses a phenomenological approach, with the study subjects being online loan debtors who work as accountants. The results of this study conclude that accounting based on the Pancasila perspective has motivated and guided accountants in resolving their financial problems related to online loans. This finding is relevant to the results of previous studies that show that accounting has various perspectives, one of which is based on the Pancasila perspective. This study has proven previously at the practical level. This study fills the research gap on the role of Pancasila perspective accounting by presenting the experience of accountants as online loan debtors. Practically, this study offers the role of Pancasila perspective accounting in unraveling financial problems such as online-based loan traps to various parties.